Beyond the War: Nazi Propaganda Aims in Spain during the Second World War. (October 2019) - Peñalba-Sotorrío, Mercedes
This article argues that the objectives pursued by Nazi propaganda in Spain went far beyond merely securing Spanish participation in the Second World War. Through the examination of under-utilized materials from Spanish and German archives, including the previously inaccessible archive of José Luis de Arrese, general secretary of the Falange, this article shows that propaganda campaigns varied in means, content and dissemination, depending on the evolution of the conflict. The aims of these campaigns reflect in turn Nazi interests in Spain, from protecting economic assets in the Peninsula, to ensuring the supply of raw materials to the war effort, and turning Spain into a bridgehead for German interests in North Africa and Latin America. The article shows how a combination of ideology and opportunism, conveniently balanced by the ambassadors' realpolitik, allowed for fruitful collaboration with the Falange. This was central to the development of the propaganda campaigns. I contend that by looking more closely at the ramifications of Spanish neutrality, we can further analyse how Spain fitted into the Nazis' overarching foreign policy and evaluate whether this was the product of opportunism or historical continuities with pre-war policies, including German propaganda aims in Spain during the First World War.